The Tragedy of the Period in the Stories of Abdulla Qahhor (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyzes the tragedy of the period in Abdullah Qahhor’s stories. It also focuses on the significance of the author's stories for that period. In the analysis of the article, the methods of comparative, sociological analysis were used